Medical Perceptions of the Unborn in Early 19th Century America (1800-1865) - Fortin, Suzanne (Université d'Ottawa / University of Ottawa, 2023)
This study explores the genesis of the presence of the fetus in American culture by examining the evolution of American medical attitudes towards the unborn (1800-1865) in the lead up to the Physicians Crusade Against Abortion in the mid 19th century. Specifically, it analyzes how American allopathic physicians reconciled their denunciation of abortions for reproductive limitation with their approval of abortions for medical reasons, shedding light on how American physicians resolved maternal-fetal conflict. The study begins with an exploration of the medicalization of childbirth in the 18th century and how it created medical concern for the fetus. The forceps could spare the pregnant woman the craniotomy operation (collapse of the fetal skull) and save the fetus. However, not all cases of obstructed labour could be solved with the forceps, and as physicians displaced midwives as the principal birth attendants, they were confronted with the prospect of performing craniotomy on a live fetus. As they dreaded this outcome, they proposed two operations to circumvent it: the Caesarean section and induced premature labour. This shows that medicalization created concern for the fetus, particularly in the later stages of pregnancy. With new embryological research in the 1820s, concern for the fetus was extended to all stages of pregnancy and expressed itself in advice to women to guarantee a healthy child. The publication of Alfred Velpeau’s Principles of Tokology and Embryology was influential because it both normalized the fusion of embryology and obstetrics, and it justified recourse to early abortion in cases of contracted pelvises. Indications for the medical use of abortion began to multiply as a result of this shift, even as physicians denounced clandestine abortion and sought to criminalize it. This study argued the medical ideology of vitalism, as articulated by Xavier Bichat, was key in resolving maternal-fetal conflict in favour of the pregnant woman. Vitalism characterized fetuses as having the same functions as a plant and this lower level of functioning justified the sacrificing of fetal life in certain circumstances. Vitalism also viewed women to as having more sensibility, more cerebral activity, and more social ties. Therefore, women were viewed as the more deserving human being in maternal-fetal conflict.
Keywords: Abortion; History; Embryology; United States; Obstetrics; 19th Century; Midwifery; Fetus; Vitalism; Medicine; American; Craniotomy; Caesarean Section; Biology; Women; Doctors